Lancang‐Mekong Cooperation and policy actors' coalition behavior around hydropower development in the Mekong countries: Testing the impact of coalition opportunity structures. - He, Linlang; Wills, Kate; Benson, Claire; Flaim, Amanda (Review of Policy Research, 2026)
The Advocacy Coalition Framework (ACF) literature has long discussed coalition opportunity structures' (COSs) ability to shape the composition, resources, and strategies of coalitions. Yet, more empirical work is needed to understand how COSs explain coalition behavior across political systems. Guided by the ACF, this study uses English newspaper articles from the lower Mekong countries to analyze the composition of coalitions and policy actors' coalition behavior in these countries' hydropower policy subsystem around the establishment of the Lancang‐Mekong Cooperation (LMC), a China‐led initiative for regional governance. Our results reveal significant variations in COSs across the countries we studied. These variations in COSs help explain some of the observed differences in the composition of coalitions and non‐state actors' coalition strategies across these countries. Moreover, despite operating within authoritarian regimes with generally restrictive COSs, members of various advocacy coalitions actively adjust their short‐term coordination networks following LMC's establishment. Our study contributes to the thin literature on COSs' utility in explaining coalition behavior and enriches ACF's application in non‐democratic political systems. Our study also helps understand the influence of subregional collaborative frameworks on hydropower development in the Mekong region.